Digitalisasi Pembelajaran Bahasa Arab: Tantangan dan Hambatan Teungku Dayah Salafi Aceh - Muslimah, Hidayatil; Sari, Umi Yulia (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2025)
This research aims to explore and analyze the teaching of the Arabic language at Dayah Salafiyah in Aceh, examining the use of digital media in the teaching of Nahw and Sarf, as well as understanding the challenges and obstacles faced by the Teungku of Dayah in the era of digital advancement. Dayah Salafiyah is the oldest informal educational institution in Indonesia, characterized by its classical and traditional teaching methods. The development of digital electronic media has introduced a new dynamic, gradually adopted by the Teungku of Dayah to assist in teaching. This research employs a qualitative method, with data collection conducted through interviews and observations. The results show that the digitalization of Arabic language learning in Dayah Salafiyah in Aceh has not been fully optimized, facing challenges such as the lack of infrastructure/facilities, limited human resources proficient in digital media, and concerns that the use of digital media might have negative impacts on students, potentially decreasing their motivation to learn and leading to distractions